The malignant melanoma of pedis: A rare case report of Dr. Soetomo general state hospital - Larasati, Nikita Gladys; Ali, Iskandar (Edelweiss Applied Science and Technology, 2025)
Melanoma is a malignant tumor (cancer) that originates from skin pigment-producing cells, melanocytes. Currently, 1 in 28 men and 1 in 44 women will be diagnosed with skin melanoma during their lifetime. Mr. R, 67 years old, complained of a wound that did not heal for approximately 1 year, after which a mass appeared. On physical examination, the mass was found to be hard, red, and wet, with no visible pus or ulcers. Anatomical pathology results showed metastatic malignant melanoma in the left inguinal region. In this case, a picture of malignant melanoma was found that resembled squamous cell carcinoma and did not exhibit features of conventional malignant melanoma (ABCD). During the diagnostic process, a hard solid mass was identified, which does not typically disguise a lesion in malignant melanoma located on the plantar surface. The patient underwent definitive therapy, which included wide excision, amputation of digits 4 and 5 of the foot, and left inguinal dissection, as well as radicality of the surgical margins. It is important to diagnose patients more quickly by understanding the history of the patient’s complaints, conducting a detailed physical examination, and performing appropriate supporting examinations so that treatment can be initiated promptly.